Analisis perbandingan Harga Saham PT. Bank Mandiri Persero (tbk.), PT. Bank Rakyat Indonesia Persero (tbk), PT. Bank Negara Indonesia Persero (tbk) Sebelum dan Sesudah Danantara Diresmikan - Sefnando, Agabril; Nugraha, Budi Sutiono Pratama (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the impact of the inauguration of Danantara on the share prices of three state-owned banks, namely PT Bank Mandiri (BMRI), PT Bank Rakyat Indonesia (BBRI), and PT Bank Negara Indonesia (BBNI). The method used is an event study with an observation period of ±30 days before and after February 24, 2025 as the event date. Secondary data in the form of daily stock closing prices were obtained from Yahoo Finance and analyzed using descriptive statistics, normality tests, and Paired-Sample T-tests. The results of the study show that there was a significant decrease in the share prices of the three banks after the inauguration of Danantara. BMRI experienced the largest average decrease, followed by BBRI and BBNI, with a significance value of the t-test < 0.001 in all samples. These findings indicate that the market responded negatively to the event, reflecting investor uncertainty about the direction of government policy and potential risks to the state-owned banking sector. In practical terms, these results confirm the importance of information transparency, communication strategies, and risk management by banking management in mitigating the impact of negative market perception. This research also enriches the literature of event studies in emerging markets by providing empirical evidence on the sensitivity of state-owned banking stocks to strategic public policies.